Understanding the multifaceted roles of the phosphoenolpyruvate: Phosphotransferase system in regulation of Salmonella virulence using a mutant defective in ptsI and crr expression - Lim, Sangyoung; Seo, Ho Seong; Jeong, Jisu; Yoon, Hyunjin (Microbiological Research, 2019)
The phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS) catalyzes the translocation of sugar substrates with their concomitant phosphorylation in bacteria. In addition to its intrinsic role in sugar transport and metabolism, numerous recent studies report the versatility of the PTS to interconnect energy and signal transduction in response to sugar availability. In this study, the role of PTS in Salmonella virulence regulation was explored. To decipher the regulatory network coordinated by the PTS during Salmonella infection, a transcriptomic approach was applied to a transposon insertion mutant with defective expression of ptsI and crr, which encode enzyme I and enzyme IIAGlc of the PTS, respectively. There were 114 differentially expressed genes (DEGs) exhibiting two-fold or higher expression changes in the transposon mutant strain, with 13 up-regulated genes versus 101 down-regulated genes. One-third of the DEGs were associated with energy production and carbohydrate/amino acid metabolism pathways, implicating the prominent role of the PTS in carbohydrate transport. With regard to regulation of virulence, the tested mutant decreased the expression of genes associated with quorum sensing, Salmonella pathogenicity islands, flagella, and the PhoPQ regulon. We investigated the possibility of PTS-mediated regulation of virulence determinants identified in the transcriptomic analysis and proposed a regulatory circuit orchestrated by the PTS in Salmonella infection of host cells. These results suggest that Salmonella divergently controls virulence attributes in accordance with the availability of carbohydrates in the environment.
Keywords: Phosphotransferase system; ptsI; Regulation; Salmonella typhimurium; Transcriptomics; Virulence; Bacterial Proteins; Biological Transport; DNA Transposable Elements; Flagella; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Membrane Proteins; Mutation; Phosphoenolpyruvate; Phosphorylation; Phosphotransferases; Regulon; Salmonella; Salmonella Infections; Salmonella typhimurium; Signal Transduction; Transcriptome; Type III Secretion Systems; Virulence; Virulence Factors; Carbohydrate phosphotransferase system (PTS); ptsI; Regulation; Salmonella Typhimurium; Transcriptomics; Virulence